Exocyclic Control of Turn Induction in Macrocyclic Peptide Scaffolds. Issue 52 (20th November 2013) - Zaretsky, Serge; Scully, Conor C. G.; Lough, Alan J.; Yudin, Andrei K.
<x xml:space="preserve">Abstract</x> Modification of a peptide: The combination of aziridine aldehyde based peptide cyclization and aziridine ring‐opening chemistry furnishes peptides with well‐defined secondary structure. An exocyclic amide, which is a product of the cyclization reaction, forms a number of intramolecular hydrogen bonds, thereby leading to increased scaffold rigidity and cellular permeability (see scheme).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>